A Comparative Structure and Performance Study of La1-xSrxCoO3-δ and La1-xSrxCo0.9Nb0.1O3-δ (x = 0.5, 0.7, 0.9, and 1.0) Oxygen Permeable Mixed Conductors - Zhao, J.; Sunarso, J.; Zhou, W.; Shao, Z.; Ran, R.; Liu, Shaomin (The Electrochemical Society, Inc, 2011)
In this work, we investigate and contrast the perovskite structure of La1-xSrxCoO3-δ and La1−xSrxCo0.9Nb0.1O3-δ (both for x = 0.5, 0.7, 0.9, and 1.0) as well as their oxygen nonstoichiometry, oxygen bulk-diffusion, and surface exchange coefficients to describe their distinct performance as ceramic oxygen ionic transport membranes. Le Bail refinements of x-ray diffraction data demonstrate that except for SrCoO3-δ, the structure for all title compounds at room temperature can be fitted adequately using rhombohedrally distorted perovskite structure. The presence of lanthanum is found to reduce the solubility of niobium in perovskite lattice. Aside from SrCo0.9Nb0.1O3-δ, structure deterioration or transformation occurs for all title compounds upon subjected to modest reducing atmosphere of nitrogen. Oxygen permeation testing reveals that Sr0.9Co0.9Nb0.1O3-δ membrane exhibits the largest fluxes among all the title compounds, followed by La0.1Sr0.9Co0.9Nb0.1O3-δ and La0.1Sr0.9Co0.9Nb0.1O3-δ and La0.1Sr0.9CoO3-δ. The oxygen permeation values exhibit exact the same trend as a function of composition with the bulk-diffusion and surface exchange coefficients values indicating both bulk-diffusion and surface exchange limits the oxygen transport through title compounds. In addition, 300-hour permeation testing on the best doped compounds, La0.1Sr0.9Co0.9Nb0.1O3-δ and La0.1Sr0.9CoO3-δ demonstrates that La0.1Sr0.9CoO3-δ has better performance stability, e.g. lower degradation percentage with time relative to its non niobium doped counterpart.